Influence of HPMC and SF on buildability of 3D printing foam concrete: From water state and flocculation point of view. (1st August 2022) - Liu, Chao; Chen, Yuning; Xiong, Yuanliang; Jia, Lutao; Ma, Lei; Wang, Xianggang; Chen, Chun; Banthia, Nemkumar; Zhang, Yamei
Abstract: Due to the intrinsic high flowability of foam concrete (FC), it is challenging to achieve good buildability for 3D printing of FC. In this paper, the effects of hydroxypropyl methylcellulose (HPMC) and silica fume (SF) on the rheological properties and buildability of 3D printing FC (3DPFC) were studied from the evolvement point of the flocs and the state and distribution of water in the mixture. Flocculation structural models of 3DPFC doped by SF and HPMC were proposed. HPMC improves the yield stress and the buildability of FC by agglomerating cement particles into large and ultra-large flocs. SF does not significantly increase the proportion of ultra-large flocs, but considerably reduce the free water movement due to its adsorption on the surface and the formation of flocs composed of SF particles or SF and cement particles. In addition, the re-flocculation ability of SF flocs can significantly contribute to the thixotropy and buildability of 3DPFC.